Mini-Hydraulic Generation System for Puerto Eden, Chile - Chavez-Orostica, H (Institute of Electrical and Electronics Engineers Inc., 2021)
In general, isolated locations are a challenge to provide electrical power. One of these places is Puerto Edén, in Chile, which has a very restrictive electricity service based on Diesel Generation. However, the geographical location has a hydroelectric potential that is not well exploited. This paper presents a case study on the design of a micro hydroelectric plant for Puerto Edén. Calculations of basic parameters for design, estimation of electrical consumption through statistical curves and the process for choosing electromechanical equipment are show. Finally, the design is checked using a simulation in Digsilent. The idea is to provide a baseline approach to isolated locations with hydroelectric potential and to help the Puerto Edén community to understand the resources available to them. © 2021 IEEE.